2021
DOI: 10.1101/2021.02.09.21250257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Perceptions, Knowledge and Behaviors of General and High-Risk Adult Populations towards COVID-19: A Systematic Scoping Review

Abstract: Background: The COVID-19 pandemic represents a major crisis for governments and populations around the globe. A large number of studies have been conducted worldwide to understand people's awareness and behavioral response towards the disease. The public's risk perceptions, knowledge, and behaviors are key factors that play a vital role in the transmission of infectious diseases. Our scoping review aims to map the early evidence on risk perceptions, knowledge, and behaviors of general and high-risk adult popul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…COVID-19 patients in Wuhan China and waiters in Southern Ethiopia Zhong et al (2021) and Asefa et al (2020)respectively found respondents had a higher risk perception of the COVID-19. During the first wave of COVID-19, a systematic study found that the perceived seriousness of the disease was significantly higher than the perceived vulnerability to haveing COVID-19 (Clavel et al, 2021).…”
Section: Level Of Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 patients in Wuhan China and waiters in Southern Ethiopia Zhong et al (2021) and Asefa et al (2020)respectively found respondents had a higher risk perception of the COVID-19. During the first wave of COVID-19, a systematic study found that the perceived seriousness of the disease was significantly higher than the perceived vulnerability to haveing COVID-19 (Clavel et al, 2021).…”
Section: Level Of Risk Perceptionmentioning
confidence: 99%
“…Gloves, surgical masks, N95 masks, protective glasses, disposable aprons/overalls, and aprons/jerseys were all used at a rate of 96.6%, 98%, 36%, 21%, 12%, and 22%, respectively (Arslanca et al, 2021). A systematic review conducted on adult found that they were knowledgeable about protective behaviours such as hand-washing, mask-wearing, social distancing, and avoidance behaviours (Clavel et al, 2021).…”
Section: Health Protective Behavioursmentioning
confidence: 99%
“…As such, countries, governments, and organizations have dedicated a considerable amount of attention to identifying, examining, and researching the various impacts of the pandemic on systems, communities, and individuals. This research agenda has led to the publication of thousands of primary studies and evidence syntheses on prevention and control methods, 1 redesigning health services, 2 challenges with using telemedicine, 3 mental health issues among health care providers, 4 risk perceptions and behaviors of the general population, 5 and more. Evidence syntheses perform rigorous and systematic investigations of the primary literature to provide knowledge about an unknown topic in order to augment decisionmaking.…”
Section: Introductionmentioning
confidence: 99%